APPLICATION OF RECOMBINANT TRIACYLGLYCEROL LIPASE AND CARBOXYLESTERASE ENZYMES FROM Bacillus velezensis STRAIN S3 FOR POLYESTER SURFACE MODIFICATION (Balai Bioteknologi, Badan Pengkajian dan Penerapan Teknologi (BPPT), 2022)
ABSTRACT Enzymatic polyester surface modification can be performed with lipase and esterase enzymes. In this study, the polyester fabric modification utilized triacylglycerol lipase (TGA) and carboxylesterase (CES) recombinant enzymes. The effect of these treatments was observed by determining the hydrophilicity level, dye absorption level, hydroxyl group measurement, and fiber surface morphology. The results revealed an elevated hydrophilicity level in polyester fabric, followed by dye absorption improvement and carboxyl group increase. The water absorption times required by the fabric based on the results of TGA, CES, comparative lipase, and negative control treatments were 3±0.05 seconds, 3.5±0.07 seconds, 5±0.05 seconds, and 80±11.54 minutes, respectively. Dye absorption test in polyester fabric based on these groups mentioned above were 52±0.5, 58±0.5, 178±0.5, and 2968±290 seconds. The total hydroxyl group measurement in polyester fabric was observed at 30.9±0.09, 30.5±0.05, 28.6±0.09, and 3 meq/100 g. The SEM observation showed that the enzymatic hydrolysis could alter the porous structure and surface of the fibers. ABSTRAK Modifikasi permukaan poliester secara enzimatis dengan enzim lipase dan esterase mengubah poliester menjadi hidrofilik. Pada penelitian ini, modifikasi permukaan poliester menggunakan enzim rekombinan Triasilgliserol lipase (TGA) dan Karboksilesterase (CES). Parameter uji meliputii hidrofilisitas, penyerapan warna, pengukuran gugus hidroksil, dan morfologi permukaan serat. Hasil hidrolisis menunjukkan peningkatan hidrofilisitas, penyerapan warna dan gugus karboksil kain poliester. Waktu penyerapan air oleh kain hasil perlakuan enzim TGA, CES, lipase pembanding dan kontrol negatif berturut-turut adalah 3±0,05, 3,5±0,07, 5±0,05 detik dan 80±11,54 menit. Uji serapan warna kain poliester pada kelompok tersebut diatas berturut-turut adalah 52±0,5, 58±0,5, 178±0,5 dan 2968±290 detik. Pengukuran jumlah gugus hidroksil pada kain poliester perlakuan TGA, CES, enzim lipase pembanding dan kontrol negatif adalah 30,9±0,09, 30,5±0,05, 28,6±0,09 dan 3 meq/100 g. Hasil SEM menunjukkan adanya perubahan struktur pori dan permukaan serat.